2019
DOI: 10.1016/s2214-109x(18)30567-9
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision to prevent HIV and other sexually transmitted infections in men who have sex with men: a systematic review and meta-analysis of global data

Abstract: Background Men who have sex with men (MSM) are disproportionately affected by HIV and other sexually transmitted infections (STIs) worldwide. Previous reviews investigating the role of circumcision in preventing HIV and other STIs among MSM were inconclusive. Many new studies have emerged in the past decade. To inform global prevention strategies for HIV and other STIs among MSM, we reviewed all available evidence on the associations between circumcision and HIV and other STIs among MSM.Methods In this systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 90 publications
(157 reference statements)
1
66
0
1
Order By: Relevance
“…250 A more recent metaanalysis, involving 62 observational studies and 119 248 MSM, found MC was associated with a significant, overall 23% reduced risk of HIV infection among MSM (OR 0.77; 95% CI 0.67-0.89). 251 the implications of which were further discussed in an accompanying editorial. 252 Each meta-analysis referred to the highly significant 89% risk reduction conferred by MC to insertive MSM in Sydney, Australia, 253 and called for more studies of MSM who adopt the insertive role during anal intercourse, as well as more studies of bisexual men because of the risk of STI transmission they pose to women.…”
Section: Hiv Infection In Men Who Have Sex With Men (Msm)mentioning
confidence: 97%
See 2 more Smart Citations
“…250 A more recent metaanalysis, involving 62 observational studies and 119 248 MSM, found MC was associated with a significant, overall 23% reduced risk of HIV infection among MSM (OR 0.77; 95% CI 0.67-0.89). 251 the implications of which were further discussed in an accompanying editorial. 252 Each meta-analysis referred to the highly significant 89% risk reduction conferred by MC to insertive MSM in Sydney, Australia, 253 and called for more studies of MSM who adopt the insertive role during anal intercourse, as well as more studies of bisexual men because of the risk of STI transmission they pose to women.…”
Section: Hiv Infection In Men Who Have Sex With Men (Msm)mentioning
confidence: 97%
“…A Cochrane meta‐analysis concluded that, “ Current evidence suggests that male circumcision may be protective among MSM who practice insertive anal sex, but the role of male circumcision overall in the prevention of HIV […] among MSM remains to be determined .” The meta‐analysis found a 73% decrease in HIV infection risk in studies of MSM reporting an insertive role during anal intercourse, but no significant difference in studies of men reporting a receptive role . A more recent meta‐analysis, involving 62 observational studies and 119 248 MSM, found MC was associated with a significant, overall 23% reduced risk of HIV infection among MSM (OR 0.77; 95% CI 0.67‐0.89) . the implications of which were further discussed in an accompanying editorial .…”
Section: Physical Harmmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that circumcision is associated with remarkably reduced odds of penile HPV infection among MSM. Male circumcision leads to a decreasing number of host cells for HPV to infect, removing microenvironments that support the replication and survival of HPV, and decreasing the risk of microabrasions during sexual intercourse that facilitates the entry of HPV into the body [169]. The estimated prevalence rate of male circumcision is approximately 38.7% across the world [170], and it is a routine practice for Muslims and Jews [171].…”
Section: Moreover the Transmission Of Hiv Is Facilitated By The Lesimentioning
confidence: 99%
“…Preventive measures against HPV acquisition include circumcision in males [5], use of condom [6], and HPV vaccination [7]. Utilization of the condom is deficient among MSM [8], especially since the availability of pre-exposure prophylaxis to reduce the risk of HIV transmission [9].…”
mentioning
confidence: 99%